Characterization of phosphate solubilizing plant growth promoting rhizobacterium Lysinibacillus pakistanensis strain PCPSMR15 isolated from Oryza sativa - Lelapalli, Srilakshmi; Baskar, Samundeeshwari; Jacob, Sharon Maria; Paranthaman, Sripriya (Current research in microbial sciences, 2021)
•Lysinibacillus pakistanensis PCPSMR15, a potential bacterium isolated from rice rhizosphere is capable of solubilizing inorganic phosphorus from insoluble compounds.•This bacterium exhibited halo tolerant ability and also demonstrated qualitative production of various enzymes of biotechnological and industrial applications.•Efficient producer of Indole acetic acid and promoted plant growth in terms of length of root, shoot and leaf.•L. pakistanensis PCPSMR15 with remarkable plant growth promoting traits, thus may play an important role in increasing the soil fertility and development of eco-friendly sustainable agriculture. The rhizosphere soil is a source for a diversity of microorganisms which play a vital role in the enhancement of plant health through the mechanism of symbiotic interaction thereby influencing the plant growth. The present study aimed at isolating potential phosphate solubilizing rhizobacteria from rice (Oryza sativa) crop for which, four different rhizosphere soil samples were collected from different locations of Tiruvallur district, India. Isolates were cultured on nutrient agar medium followed by serial dilutions and different colonies with morphological variations were isolated from each dilution. A total of 52 bacteria were isolated and maintained as pure cultures. Out of the 52 isolates, 16 strains showed phosphate solubilizing ability and amongst them, 4 were highly potential which were subjected to morphological and biochemical characterization. Phosphate solubilizing bacterial strains when assessed for their possible effect of their inoculation on the growth and development of mung bean seeds significantly enhanced the growth of the plants. Furthermore, the potential bacteria were analysed for Indole Acetic Acid (IAA) production, which was found to be directly proportional to the plant growth promotion. Upon the comparative analysis of the four potential isolates, PCPSMR15 exhibited remarkable plant growth promoting traits. A detailed biochemical and molecular analysis identified the promising strain PCPSMR15 as Lysinibacillus pakistanensis. The present study, thus signifies the strain, PCPSMR15 for exploration as an inoculant for improving soil fertility, enhancing phosphorus availability to plants and improved crop production and sustainability.